Development of an ICT-based Interactive Training Module in Improving Organizational Development Competencies for Elementary School Principals - Nilawati, Nilawati; Rusdinal, Rusdinal; Subandi, Ahmad (International Conference on Elementary Education, 2020)
The abstract The development of an ICT-based interactive training module to improve organizational development competencies for elementary school principals uses the Kvisoft Flipbook Maker application and Adobe Flash Software, which is an effort for principals to feel stimulation in independent learning. This study aims to produce ICT-based training module products. This type of research is research development known as (Research & Development). The product validity test was conducted by four validators consisting of two material experts and two media experts. The practicality test was carried out on the principal of the Nanggalo subdistrict elementary school. Practicality test subjects were taken as many as 14 principals to test the practicality of ICT-based training module products. The results showed that ICT-based interactive training modules in improving organizational development competencies for elementary school principals were very valid. This means that the training modules for elementary school principals are of good quality to be used based on expert material assessments with an average rating of 82.34% in the very valid category and media expert ratings with an average rating of 83.07% in the very valid category. For the principal's practicality test, categorizing ICT-based interactive training modules is very practical because of its ease of use with an average count of 3.56 and a percentage value of 89%. Thus it can be concluded that ICT-based interactive training modules in improving organizational development competencies for ICT-based primary school principals are declared to be very valid and very practical